Epithelioid hemangioendothelioma with extensive cystic change and CAMTA1 rearrangement. (18th October 2013) - Lee, Seung Eun; Park, Ha young; Kim, Seokhwi; Bang, Heejin; Min, Ji Hye; Choi, Yoon‐La
Abstract : Epithelioid hemangioendothelioma (EHE) is a rare vascular neoplasm that has the ability to recur locally and metastasize. Thus, it is important to distinguish this tumor from other epithelioid vascular neoplasms. A 47‐year‐old man presented to our hospital with a pelvic mass with severe ischialgia and weight loss. Surgical resection was performed, and the mass was found to have dark red multiloculated cysts with hemorrhage and calcification. The histopathologic examination showed a central sclerotic, hypocellular zone and a peripheral cellular zone. Only the peripheral portion of the wall revealed nested tumor cells in light blue myxoid stroma. These tumors are typically composed of short strands or cords of bland epithelioid cells with occasional intracytoplasmic lumens embedded in a myxohyalinized stroma. The tumor cells were positive for CD31 and CD34 and negative for factor VIII‐related antigen, CK (AE1/AE3) and S‐100. The tumor nuclei showed distinct break‐apart signals with individual green and/or red signals, indicating the presence of CAMTA1 rearrangement. In this study, we report a case of EHE that was difficult to diagnose based on histology alone. Therefore, we also performed fluorescence in situ hybridization, and found that the tumor harbored a CAMTA1 gene rearrangement, which confirmed the diagnosis.